Hubungan Merokok terhadap Kejadian Hipertensi Di Kabupaten Pidie Jaya - Nuriani Nuriani; Kintoko Rochadi; Fazidah Aguslina Siregar (Syntax Corporation Indonesia, 2021)
Lifestyle is one of the factor than can influence healthy living behavior. Hypertension is one of the non communicable diseases caused by lifestyle pattern, where hypertension is one of the disease than can trigger other diseases such as heart disease and stroke. The prevalence of hypertension in Aceh reached 27,8 percent in 2018 and the prevalence of hypertension in Pidie Jaya reached 23,4 percent in the same year. This study aims to determine the relation of smoking on the incident of hypertension in Kabupaten Pidie Jaya. This type of study was quantitative with analytic, research using crosssectional design. The sample are 270 samples obtained using multistage random sampling by combining three sampling techniques in stages. The instrument in this study was questionnaire. Data obtained in this study were analyzed by univariate and bivariate using simple logistic regression tests. The results showed that there were influences of smoking (p =0,002), long time smoking (p = 0.358) number of cigarattes (p=0,931) on the incidence of hypertension. Meanwhile there is no relation of kind of coffee (p=0,876). Health officer must active give health education and active establishing cooperation with community components as an effort to reduce the incidence of hypertension through campaigns against the danger of smoking.